(untitled) (Palíndromo, 2023)
This article presents portraits of women who had romantic relationships with other women, through the work of two lesbian photographers: Berenice Abbott and Gisèle Freund. The photographs of both artists were taken mainly within the European artistic circle, especially in Paris, during the first half of the 20th century. In addition to exploring the photographers biographies and their productions, aspects of the life and work of each portrayed woman will also be discussed; among them are the artists and writers Marie Laurencin, Colette, Djuna Barnes and Janet Flanner. Through this research, it was possible to observe the importance of creating bonds between these women, highlighted by the exchange of glances between photographer and photographed, to support a sense of community and construction of an identity among lesbian women. Thus, this article seeks to expand the reflection on lesbian women in art historiography and reaffirm the relevance of making visible the relationships between women, which, for a long time, were largely hidden.